Presidential rhetoric and cybercrime: tangible and symbolic policy statements - Hill, Joshua B. (Criminology, criminal justice, law & society, 2016)
In today’s digital age, new kinds of crime are continually emerging. If cybercriminals attack businesses and individuals, the results can be devastating.Although most people take precautions to prevent becoming a victim of cybercrime (i.e. firewalls, complex passwords), they are still concerned about the potential of becoming a victim. They will often put pressure on government officials and demand that action be taken to lessen the possibility of another cybercrime attack. Elected officials, particularly presidents, have begun to more often speak about the dangers of cybercrime and suggest possible solutions. To date, there is relatively little analysis of what presidents are saying about cybercrime and how they are speaking about it. This paper aims to fill that gap that currently exists in the literature by looking at patterns and trends in presidential rhetoric on cybercrimes. Specifically, this study examines whether presidents talk about cybercrime in substantive or symbolic terms. Do they give precise and action able options in their rhetoric or more “feel good” statements? It was predicted that, given the complexity of thetopic, presidents will use more symbolic rhetoric to speak about cybercrime rather than tangible policy language. The findings suggest this to be true. We also attempt to draw some conclusions about why presidents may be drawn to symbolic rhetoric regarding cybercrime.